2003
DOI: 10.1038/sj.ijo.0802475
|View full text |Cite
|
Sign up to set email alerts
|

Long-term pharmacotherapy for overweight and obesity: a systematic review and meta-analysis of randomized controlled trials

Abstract: CONTEXT: Safe and effective strategies to curb rising obesity prevalence rates are urgently needed and medications may play a more prominent role in future therapeutic regimens. OBJECTIVE: To review systematically the long-term efficacy and safety of approved antiobesity medications. DATA SOURCES: MEDLINE, EMBASE, the Cochrane Controlled Trials Register, Current Science Meta-register of Controlled Trials, and reference lists of original studies and reviews were searched. Drug manufacturers and two obesity expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
181
1
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(199 citation statements)
references
References 51 publications
(81 reference statements)
10
181
1
7
Order By: Relevance
“…First, although consistent with that of previous 1-year studies in overweight or obese patients, 49 including those done in patients with type 2 diabetes, 48 the retention rate of about 66% in all treatment groups might be considered as rather low. One should note that the dropout rate in this study was lower than in previously reported studies with rimonabant in non-diabetic patients.…”
Section: Discussionsupporting
confidence: 52%
“…First, although consistent with that of previous 1-year studies in overweight or obese patients, 49 including those done in patients with type 2 diabetes, 48 the retention rate of about 66% in all treatment groups might be considered as rather low. One should note that the dropout rate in this study was lower than in previously reported studies with rimonabant in non-diabetic patients.…”
Section: Discussionsupporting
confidence: 52%
“…117,118 We also did not assess the mechanisms, benefits, and risks of specific weight loss methods, which have been addressed elsewhere. 7,103,[114][115][116] Our findings have potential clinical implications. First, in obese people with cardiovascular risk factors, weight loss can provide some health benefits.…”
Section: Discussionmentioning
confidence: 71%
“…Our review can be differentiated from other reviews of weight loss, which included studies with a short follow-up duration, did not specify the study selection process, or did not assess applicability to clinical practice. 7,[103][104][105][106][107][108][109][110][111][112][113][114][115][116] Our review has some limitations. We did not assess supplementary weight loss methods, such as behavioral or exercise programs, when used as stand-alone interventions.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] In controlled clinical trials many efforts are undertaken to keep patients stick to the study. Intensification of contacts with care-givers has been shown to improve the outcome, at least in the short-term.…”
Section: Introductionmentioning
confidence: 99%